Sistema de emulação de aerogeradores para aplicação em geração distribuída de energia elétrica - Martinello, Diana (2015)
Power generation from alternative sources is at present the subject of numerous research and development in science and industry. Wind energy stands out in this scenario as one of the most prominent alternative in the generation of electricity, by its numerous advantages. In research works, computer reproduction and experimental behavior of a wind turbine are very suitable tools for the development and study of new technologies and the use of wind potential of a given region. These tools generally are desired to include simulation of mechanical and electrical parameters that directly affect the energy conversion. This work presents the energy conversion process in wind systems for power generation, in order to develop a tool for wind turbine emulation testing experimental, using LabVIEW® software. The purpose of this tool is to emulate the torque developed in an axis wind turbine. The physical setup consists of a three phase induction motor and a permanent magnet synchronous generator, which are evaluated under different wind speed conditions. This tool has the objective to be flexible to other laboratory arrangements, and can be used in other wind power generation structures in real time. A modeling of the wind power system is presented, from the turbine to the electrical generator. A simulation tool is developed using Matlab/Simulink® with the purpose to pre-validate the experiment setup. Finally, the design is implemented in a laboratory setup.